Design of a vacuum system for space active hydrogen maser - Que, Haohui; Xu, Wujiabei; Li, Qi; Xiang, Jie; Lu, Tao; Liu, Tiexin; Cai, Yong; Dai, Jiayu; Hou, Xueling (Frontiers in Physics, 2022)
With the high precision and stability of its frequency signal outputs, active hydrogen maser plays an important role in such fields as timing, satellite navigation, and communication. However, it needs to be lighter so as to be applied in space. We made a research, based on the calculation of the hydrogen flow and the adsorption efficiency of the adsorption unit, on the parameters of the vacuum system and the structural requirements, and designed a combined vacuum pump for the Space Active Hydrogen Maser (SAHM). This vacuum pump consists of a getter pump and a small ion pump, the total mass of which is about 5 kg. The pumping speed will be about 474 L/s by computation, when an amount, 2.5 MPa L, of hydrogen has been adsorbed by getters. Theoretically, the total source hydrogen inflow in lifetime is not higher than 20% of the total capacity getter pump, thus the design should amply meet the requirements of the SAHM vacuum system, and is of great significance for future SAHM applications.